Temporalities - West-Pavlov, Russell, 1964- (London ; New York : Routledge, 2013)
"Temporalities presents a concise critical introduction to the treatment of time throughout literature. Time and its passage represent one of the oldest and most complex philosophical subjects in art of all forms, and Russell West-Pavlov explains and interrogates the most important theories of temporality across a range of disciplines. The author explores temporality's relationship with a diverse range of related concepts, including: - historiography - psychology - gender - economics - postmodernism - postcolonialism. Russell West-Pavlov examines time as a crucial part of the critical theories of Newton, Freud, Ricoeur, Benjamin, and explores the treatment of time in a broad range of texts, ranging from the writings of St. Augustine and Sterne's Tristram Shandy, to Woolf's Mrs Dalloway and Stoppard's Rosencrantz and Guildenstern are Dead. This comprehensive and accessible guide establishes temporality as an essential theme within literary and cultural studies today"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Literature -- History and criticism -- Theory, etc; Time in literature; Electronic books